Impact of hypoxia on alveolar bone dynamics and remodeling - Sangeetha Narasimhan; Sausan Al Kawas; Shishir Ram Shetty; Hiba Saad Al-Daghestani; Rani Samsudin (Heliyon)
Oxygen is a fundamental requirement for cellular metabolism. Hypoxia is a state of oxygen deprivation of the tissues. Cells develop numerous adaptive mechanisms to survive hypoxic insult. Alveolar bone is a unique structure that encases and protects the tooth. Literature reports that hypoxia, in all forms, impacts alveolar bone health. The hypoxia-inducible pathway appears to play a key role in mediating changes in alveolar bone metabolism. Embryonic hypoxia plays a vital role in craniofacial skeletal development. Further, hypoxia has been anticipated in the repair of extraction sockets. Alveolar bone cells respond distinctly to hypoxic conditions with both beneficial and detrimental effects. Studies have demonstrated enhanced alveolar bone resorption upon hypoxic stimuli. However, hypoxia has also been shown to have potential therapeutic effects on alveolar bone by triggering an angiogenic response. Additionally, the type, duration, and mode of hypoxia are critical in triggering varied responses in alveolar bone metabolism. The main objective of this review is to recapitulate the effects of different types of hypoxia on the tooth supporting apparatus and to analyze some of the presumptive mechanisms underlying hypoxia-induced changes in alveolar bone remodeling.